Visual Narratives of Crime on Instagram: Storytelling Strategies of the Main Chilean TV Channels in 2023-2024 - Crisóstomo Flores, Paz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This research analyses the visual narratives and storytelling strategies in crime-related posts on Instagram by Chile’s major free-to-air television media outlets (2023–2024). Employing a mixed-methods approach, it examines framing, visual formats, levels of interaction, and narrative tone. The findings reveal a tension between the need to inform and attract audiences, underscoring the impact of sensationalism, emotionality, and virality on crime perception. The study discusses how media practices in constructing criminal narratives pose challenges to the ethical and social implications of the media.